Simplified Small-Signal Model for Output Voltage Control of Asymmetric Cascaded H-Bridge Multilevel Inverter - Curi Busarello, Tiago Davi; Mortezaei, Ali; Morales Paredes, Helmo Kelis [UNESP]; Al-Durra, Ahmed; Pomilio, Jose Antenor; Simoes, Marcelo Godoy (Ieee-inst Electrical Electronics Engineers Inc, 2018)
This paper proposes a simplified small-signal model for output voltage control of a single-phase asymmetrical cascaded H-bridge multilevel inverter (ACHMI). The ACHMI is an n-series connected H-bridge converter, each one with a unique value at the dc link and usually scaled at {1:2:6:...} or {1:3:9:...}. By assuming that the small-signal variation component is equal in all n converter terminal ports, a simplified small-signal model is obtained. This assumption is carefully described and justified. To verify the veracity of the proposed model, two distinct control strategies are applied. One is a single-loop control scheme based on a modified proportional-integral (PI) controller. The other one is a double-loop control scheme based on a PI controller with feedforward action of the load current. Both controllers are tuned based on the dynamic behavior of the proposed model. Since the designed controllers based on the simplified model make the ACHMI output voltage to follow the reference without steady-state error, the proposed simplified model truly represents the inverter. Experimental results show the efficacy of the simplified model of the ACHMI through the two mentioned control strategies as well as the ACHMI installed in a microgrid.
Keywords: Modeling; multilevel inverter; small-signal; stair-case modulation; voltage control